2017
DOI: 10.1136/jclinpath-2016-203998
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GRK2 and IGF1R in hepatocellular carcinoma: clinicopathological and prognostic significance

Abstract: Our data indicate that GRK2 and IGF1R show a negative correlation in HCC. IGF1R could be a potential marker of poor prognosis for this malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Univariate analysis indicated that high IGF1R expression predicted poor overall and disease-free survival for patients with HCC. In multivariate analysis, IGF1R is significant in the overall survival of patients with HCC (24). Functional experiments demonstrated that IGF1R Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Univariate analysis indicated that high IGF1R expression predicted poor overall and disease-free survival for patients with HCC. In multivariate analysis, IGF1R is significant in the overall survival of patients with HCC (24). Functional experiments demonstrated that IGF1R Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…IGF1R, which is highly expressed in HCC and possibly involved in HCC formation and progression (24,25), was predicted as a potential target of miR-495 (Fig. 3A) and consequently selected for further experimental validation.…”
Section: Igf1r Is a Direct Downstream Target Of Mir-495 In Hccmentioning
confidence: 99%
“…Lin et al [23] stated similar results to us and recorded that Apo A1 sensitivity was 45% and specificity was 56% at cutoff level of 46 mg/dL.…”
Section: Discussionsupporting
confidence: 80%
“…In cases of HCC, it was recorded to be 17-53 ng/dL with mean level 32.6 mg/ dL which was agreed by Lin et al [23] who stated IGF1R level in his study to reach 33 ng/dL. In cases of cirrhotic patients, the level was decreased ranging between 17 and 53 ng/dL with a mean level 35.1 mg/dL which was agreed by Yang et al [13] and Kasprzak et al [21] who recorded the level to be 16 and 63 ng/dL, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…Its sensitivity for HCC screening ranges from 41 to 65% at a cutoff of 20 ng/mL [53][54][55][56]. In recent years, various biomarkers have emerged for diagnosing HCC and predicting patient outcome, including glypican 3 and insulin-like growth factor (IGF)II mRNA [57], Keap1 and pNrf2 [58], 3-microRNA and AFP [59], CXCL1 [60], minichromosome maintenance complex -7 [61], and IGF1 receptor [62], among others.…”
Section: Discussionmentioning
confidence: 99%